2010
DOI: 10.1029/2010ja015400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sudden stratospheric warmings on equatorial ionization anomaly

Abstract: [1] We investigate the ionospheric response to several stratospheric sudden warming events which occurred in Northern Hemisphere winters of 2008 and 2009 during solar minimum conditions. We use GPS total electron content data in a broad latitudinal region at ±40°geographic latitude and a single longitude, 75°W. In all cases, we find a strong daytime ionospheric response to stratospheric sudden warmings. This response is characterized by a semidiurnal character, large amplitude, and persistence of perturbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
289
3
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(348 citation statements)
references
References 51 publications
(66 reference statements)
48
289
3
3
Order By: Relevance
“…A similar result was reported by Goncharenko et al [2010aGoncharenko et al [ , 2010b, who noticed that the low-latitude ionosphere perturbation persisted for several days after the SSW peak. Further, a time shift has also been observed in the day maximum behavior after the stratospheric temperature peak.…”
Section: 1002/2014ja020649supporting
confidence: 74%
See 3 more Smart Citations
“…A similar result was reported by Goncharenko et al [2010aGoncharenko et al [ , 2010b, who noticed that the low-latitude ionosphere perturbation persisted for several days after the SSW peak. Further, a time shift has also been observed in the day maximum behavior after the stratospheric temperature peak.…”
Section: 1002/2014ja020649supporting
confidence: 74%
“…Earlier studies have demonstrated that the largest variations in VTEC during SSW are observed at the crests of the EIA [Goncharenko et al, 2010a;Liu et al, 2011], and the location of the crests can vary periodically by several degrees in latitude [Mo et al, 2014]. In addition, the difference from one station to another is related with superimposed perturbation caused by MSTID and/or PW disturbances.…”
Section: 1002/2014ja020649mentioning
confidence: 99%
See 2 more Smart Citations
“…The modulation of the equatorial plasma fountain has been observed in measurements of the F-region equatorial E × B drift (e.g., Chau et al 2009;Fejer et al 2011). Also, the impact on the equatorial anomaly has been revealed by ground-based and satellite measurements of the F-region plasma density (e.g., Goncharenko et al 2010aGoncharenko et al , 2010bYue et al 2010;Pancheva and Mukhtarov 2011;Lin et al 2012). Figure 48 schematically illustrates the vertical coupling of the atmosphere during stratospheric sudden warmings.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%